Access control based intelligent workshop integrated automation system based on workflow engine. (October 2020) - Liu, Yefeng; Zhao, Yuan; Li, Kangju; Yu, Shengping
Highlights: Based on access control technology, an enterprise integrated automation system and the application model based on workflow were designed. The workflow engine was designed and the structure of workflow system with custom form was given. The realization process of modern intelligent workshop integrated automation system is expounded through the hardware platform of intelligent digital factories. Abstract: With the development of modern workshop towards intellectualization, it is becoming more and more difficult to model and research the workshop integrated automation system based on workflow. Based on access control technology, an enterprise integrated automation system and the application model based on workflow were designed. Meanwhile, the workflow engine was designed and the structure of workflow system with custom form was given. The realization process of modern intelligent workshop integrated automation system is expounded through the hardware platform of intelligent digital factories. A series of automation processes such as workpiece warehousing management, digital manufacturing and processing, automatic transmission, information management, etc. are included in the system which can satisfy the concept of the intelligent digital factory and show the superiority of workflow-based enterprise integrated automation system. Graphical abstract: Image, graphical abstract